Political Dimension of Women Empowerment - Rao,Pulla (The Associated Publishers, 2011)
Women constitute slightly less than 50 per cent of the country's population in India. Despite some favourable traditional values and emergence of powerful women personalities down the ages, the position of women is not very encouraging in the country. The gender gap in India is quite strong and conspicuous in several sectors particularly in the area of political participation. The political representation by women in local, district, state and national level bodies are insignificant which is common particularly among the socially deprived sections. The contributors to the volume have examined political dimension of discrimination against women with case studies at local bodies, state and national level participation of women. The book is timely in providing data and analysis for a serious discussion on the women's reservation bill.